Política, emoções e gênero na literatura fantástica e de ficção científica de autoras brasileiras (1899-1954) - Santos, Danielle Silva Moreira dos (2024)
Rejected by both historiography and "canonical" literature, various female writers and intellectuals remained on the fringes of history. However, this silence has been progressively broken due to gender studies, which have brought to light perspectives and figures previously obscured in the traditional historical narrative. By engaging in writing, reflecting, and dialoguing with the society of their times, many women have demonstrated their presence and political action, despite the historical reluctance to recognize them as political subjects or writers. Among them, names from the fantastic literature in Brazil such as Emília de Freitas, author of "A Rainha do Ignoto" (1899), Adalzira Bittencourt, who wrote "A presidente da República no Ano de 2500" (1929), and Ada Curado, with "O sonho do pracinha" (1954), challenged the literary canon with narratives that propose alternative realities marked by equality and female leadership across different regions of Brazil. From their worldviews, they produced stories where utopia and emotions merge into acts of political resistance. This thesis aims to analyze the construction of a political pedagogy of emotions through fantastic literature by female authors and periodical press in Republican Brazil between the late 19th and early 20th centuries, establishing a dialogue with theorists of gender and emotions.